Morphometric, Meristic, and Growth Patterns of Ompok hypophthalmus Bleekerfrom the Tarai River, Tarai Bangun Village,Tambang Sub-Regency, Kampar Regency, Riau Province - Nurhasana Nurhasana; Windarti Windarti; Deni Efizon (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
AbstractOmpok hypophthalmus is freshwater fish that inhabit the Tarai River. That fish has high economic value, and it is more than Rp 60.000/kg. Information on biological aspects of this fish, including morphometric, meristic, and growth patterns, however, is rare. To understand the morphometrical, meristical characteristics and growth pattern of this fish, a research had been conducted from April-June 2018. There were 78 fishes(183-56 mm SL dan 45,32-1.23 gr BW) captured from the river. There were 25 morphological characteristics measured and 6 meristical characteristics counted. There were 7 morphometrical characteristic differences between male and female. In female fish, distance between ventral fin to the base of anal fin, height of dorsal fin, distance anal fin to the base of caudal fin, height ventral fin, and length of base caudal finare longer than those of the male, but male has longer distance mouth to the eye, and length of pectoral fin than female.The meristical characteristics were as follows: D.4, P.I.13-15, V.6-8, A.63-82, C.17-19. The length-weight relationship shown that the growth of male and female was isometric. Keywords:Sheatfish, Isometric, Morphological Characteristics, Meristical Characteristic